Fertility, Heterogeneity and the Golden Rule - Ponthière, Grégory (Global Labor Organization (GLO), 2022)
Phelpsís (1961) Golden Rule states an unambiguous relationship between optimal capital intensity and fertility: a rise in fertility decreases the optimal capital intensity, because a higher fertility increases the investment required to sustain a given capital to labour ratio (i.e., the capital dilution e§ect). Using a matrix population model embedded in a two-period OLG setting, we examine the robustness of that relationship to the partitioning of the population into 2 subpopulations having distinct fertility behaviors. We derive the optimal accumulation rule in that framework, and we show that, unlike what prevails under a homogeneous population, a rise in fertility does not necessarily reduce the Golden Rule capital intensity, but increases it when the composition e§ect induced by the fertility change outweighs the standard capital dilution e§ect prevailing under a Öxed partition of the population. We also explore the robustness of these results to a Öner description of heterogeneity, that is, a partitioning of the population into a larger number of subpopulations.
10419/264295
Keywords: Graue Literatur; Golden Rule; capital accumulation; fertility; OLG models; matrix population models; heterogeneity